Metode Mendongeng Kisah Nabi Dalam Penanaman Moral Anak Usia Dini - Kartini Kartini; Astuti Darmiyanti; Nancy Riana (UIN Sultan Maulana Hasanuddin Banten, 2022)
The problem of this research is inappropriate moral behavior that occurs in schools such as: the child doesn’t want to greet the teacher, doesn’t want to share, and still likes to annoy friens. The purpose of this study is to see an overview of instilling religious and moral values into children through the storytelling method of the prophet’s story. This study uses qualitative methods by using data triangulation, with the research subject of group B children in PAUD Miftahul Jannah Rawamerta Karawang. The result of this research is the inculcation of moral values which is carried out through storytelling activities, children’s insight becomes broad, can be motivated, able to distinguish good and bad, able to tell the contents contained in fairy tales, and can answer teacher question, so that chidren’s behavior of children after listening to fairy tales becomes moral and virtuous. Keywords: storytelling method: moral values: early childhood. References Al- Samadi,M.M.F& Alia, P. (2012). The Effect Of A Story Based Programme On Developing Moral Values At The Kingdergarten Stage. Interdisciplinary Journal Of Ccontemporary Research In Business vol 4, no 7, 534-560. Asnah. (2015). Penanaman nilai- nilai moral anak usia dini di RA DWP UIN Sunan Kalijaga Yogyakarta. Tesis magister, UIN Sunan Kalijaga Yogyakarta. Bahri, S. (2019). Urgensi Strategi Pembelajaran Karakter Pada Anak Usia Dini. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 4(2), 75–86. Essa, L. (2014). Introduction To Early Childhood Education. Canada: Wadsworth Cengange Learning. Fadillah, M& Khorida, L. M. (2016). Pendidikan Karakter Anak Usia Dini. Yogyakarta: Ar- Ruzz Media Fitriyyah, D. (2014). Pendidikan Karakter melalui Kegiatan Mendongeng. Jurnal (PAI) Pendidikkan Agama Islam. Fitriyyah, D. (2016). Membangun Karakter Anak Melalui Dongeng. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 1–10. Fitroh,F.S.(2015), Dongeng Sebagai Media Penanaman Karakter Pada Anak Usia Dini. Jurnal PG-PAUD Trunojoyo. Volume 2.Nomor 2. Oktober 2015 hal 76-149 Hafizh, Tambak. (2016). Metode bercerita dalam pembelajaran pendidikan agama islam. Jurnal Athariqah. Hughes, P. (2010). Children Play, And Development. London: SAGE Publication. Imroatun, I., Widat, F., Fauziddin, M., Farida, S., Maryam, S., & Zulaiha. (2021). Youtube as a Media for Strengthining Character Education in Early Childhood. Journal of Physics: Conference Series, 1779(1), 012064. https://doi.org/ 10.1088/1742-6596/1779/1/012064 Inawati, A. (2017). Strategi Pengembangan Moral Dan Nilai Agama Untuk Anak Usia Dini. Al- Athfal. Jurnal pendidikan anak. http://Ejournal.uin.suka.ac.id/ tarbiyah/alatfal. Jackman, H.L. (2012). Early Education A Child’s Connection to The Wordl. Australia: Wadsworth Cengange Learning. Kusumawati, I. (2016). Pengembangan Karakter Siswa Raudlatul Athfal Berbasis Pendidikan Agama Islam. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 139–148. Lenox, F. (2000). Storytelling for Young Children in a Multicultural World. Early Childhood Education Journal, Vol. 28, NO. 2. Lubis, Y. M. (2020). Penanaman Karakter Anak Usia Dini Melalui Metode Mendongeng. TAZKIR: Jurnal Penelitian Ilmu-Ilmu Sosial DanKeislaman. DOI://dx.doi.org/10.24952/tazkir.v6i1.2721 Makhmudah, S. (2020). Penanaman Nilai Keagamaan Anak Melalui Metode Bercerita. J-PAI :Jurnal Pendidikan Agama Islam. http://ejournal.uin-malang.ac/index.php/jpai McLean, Tuite. (2016). Sories And Their Values: Exploring The Role Of Storytelling In Social Care Practice. Journal Of Residential Child Care, Vol. 15, No. 2. Moleong, Lexy J. (2013). Metodologi Penelitian Kualitataif. Bandung: Remaja Rosdakarya Nurhayati, R. (2019). Membangun Budaya Literasi Anak Usia Dini dalam Keluarga. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 4(1), 79–88. https://doi.org/10.47200/JNAJPM.V4I1.918 Rahayu, S. H., Haroen, H., Budiutomo, T., Khasanah, N., & Nuryati, N. (2020). Manajemen Mutu Layanan Ta’lim Quran lil Aulad (TQA) di Yayasan Team Tadarus “AMM” Yogyakarta. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 5(2), 117–130. https://doi.org/10.47200/jnajpm.v5i2.578 Ramdani, Sari, Yuliastri. ( 2019). Penanaman nilai- nilai karakter melalui kegiatan storytelling dengan menggunakan cerita rakyat sasak pada anak usia dini, Jurnal Obsesi, Jurnal pendidikan anak usia dini. http://doi.org/10.31004/v3il.108. Rosada, D.U. (2016). Memperkuat Karakter Anak Melalui Dongeng Berbasis Media Visual. Jurnal: CARE. Children Advisory Research And Education. Safitri, LN. (2019). Pengembngan Nilai Agama Dan Moral Melalui Metode Bercerita Pada Anak. Golden Age. Jurnal tumbuh kembang anak usia dini. Safitri, N. (2019). Metode penanaman nilai agama dan moral anak usia dini. JECE Journal Of Early Childood Education. http://dx.doi.org/10.15408/ jece.vli2.13312 Salaman. (2006). Pengembangan Model- model Pembelajaran Alternatif Bagi Pendidikan Islam, Suatu Alternatif Solusi Permasalahan Pembelajaran Agama Islam. Fikrah. Santoso, F. S. (2020). Lingkungan Keluarga Sebagai Awal Pengembangan Kewirausahaan Islam. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 5(1), 13–22. https://doi.org/10.47200/jnajpm.v5i1.418 Setiani, & Nadjih, D. (2016). Pembentukan Karakter Anak Usia Dini Melalui Pendidikan Agama Islam Di TK ABA Kalibulus Rogobangsan Bimomartani Ngemplak Sleman. Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 6(2), 125–136. Utomo, B.S. (2013). Mendongeng Dalam Perspektif Pendidikan. Jurnal: Agastya. VOL 03 NO 01 JANUARI 2013 Zakiyah, N., Nurhikma, N., & Asiyah, A. (2021). Pola Asuh Orang Tua Dalam Membentuk Karakter Disiplin Anak Usia 5-6 Tahun Pada Masa Pandemi COVID-19. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(2), 127–138.